On the mesoscale mechanism of synthetic calcium–silicate–hydrate precipitation: a population balance modeling approach. Issue 2 (16th November 2017) - Andalibi, M. Reza; Kumar, Abhishek; Srinivasan, Bhuvanesh; Bowen, Paul; Scrivener, Karen; Ludwig, Christian; Testino, Andrea
Abstract : A mesoscale pathway of calcium–silicate–hydrate precipitation, leading to nanocrystallites packing nematically in anisotropic particles is quantitatively described for the first time. Abstract : Calcium–silicate–hydrate (C–S–H) is the most important product of cement hydration. Despite this importance, its formation mechanism is not well-understood. Here, we describe the novel application of a coupled thermodynamic-kinetic computational model based on a population balance equation in order to unravel the overall mechanism of synthetic C–S–H precipitation. The framework, embracing primary nucleation, true secondary nucleation, and molecular growth as the constituting sub-processes, is regressed to experimental Ca 2+ (aq) concentration vs. time data collected on a model synthetic C–S–H with Ca : Si = 2. Upon the critical appraisal of the model's adjustable parameters, which turn out to adopt rational values, simulations were performed to estimate various characteristics of the aforementioned model system ( e.g., the kinetic speciation during the precipitation process, or the mechanisms and activation free energies of nucleation and growth phenomena). We mechanistically account for the evolution of the C–S–H mesostructure which is made up of defective crystallites around 3–6 nm thick, nematically packing together in two dimensions giving rise to foil-like polycrystalline particles around 100 nm in breadth, close to the experimentally observed values. The computational framework is generic and can be applied to other precipitation systems and cement hydration scenarios.